GNSS reflectometry from low-cost sensors for continuous in situ contemporaneous glacier mass balance and flux divergence - Albin Wells; David Rounce; Louis Sass; Caitlyn Florentine; Adam Garbo; Emily Baker; Christopher McNeil (Journal of Glaciology)
Recent advances in remote sensing have produced global glacier surface elevation change data. Parsing these elevation change signals into contributions from the climate (i.e. climatic mass balance) and glacier dynamics (i.e. flux divergence) is critical to enhance our process-based understanding of glacier change. In this study, we evaluate three approaches for direct, continuous measurements of the climatic mass balance, flux divergence and elevation change at a site on Gulkana Glacier in Alaska using low-cost global navigation satellite system (GNSS) sensors, GNSS interferometric reflectometry (GNSS-IR), banded ablation stakes with time-lapse cameras and combinations thereof. Cumulative climatic mass balance over the season was 4.85 m and the three approaches were within 0.08 m through early July before the snowpack melted, and within 0.28 m through mid-August. The flux divergence increased from 0.52 ± 0.03 cm d−1 before June 3 to about 0.73 cm d−1 after June 27. We demonstrate a single GNSS system fixed atop an ablation stake can measure contemporaneous climatic mass balance, flux divergence and elevation change based on the antenna's position and GNSS-IR techniques. The ability of these systems to measure glacier mass balance and flux divergence offers unique opportunities for year-round observations on mountain glaciers in the future.